EMACIATION WITH DUAL INFECTION OF MALASSEZIOSIS AND EHRLICHIOSIS IN DOMESTIC DOG - I Nyoman Bagus Tri Aribawa; Ida Ayu Dian Kusuma Dewi; Sri Kayati Widyastuti (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Domestic dogs are frequently encountered in poor physical condition, one of which is emaciation that is often accompanied by fungal and parasitic infections, thus requiring comprehensive clinical management. This case report aims to describe emaciation accompanied by Malasseziosis and Ehrlichiosis in a 4-month-old domestic dog. Physical examination revealed a body condition score of 3/9, dermatological lesions including alopecia, papules, crusts, and scales, accompanied by a strong odor and greasy hair, as well as the presence of the tick Rhipicephalus sanguineus. Laboratory examinations included acetate tape preparation, which identified Malassezia spp., hematological analysis showing anemia and thrombocytopenia, and blood smear examination revealing Ehrlichia morulae within monocytes, which was further confirmed by a positive Ehrlichia canis antibody rapid test kit. Therapeutic management consisted of nutritional improvement through dietary modification, medicated bathing using a combination of Sodium Salicylate, Sulphur, Econazole Nitrate, and Chloroxylenol (Virbac Poison Sebazole®), administration of the antiparasitic Fluralaner (Bravecto® oral chewable tablet), Doxycycline antibiotic therapy, and supportive treatment with Livron B-plex. Evaluation on day 28 demonstrated significant weight gain, marked improvement in skin condition with resolution of alopecia, papules, crusts, and scales, reduction of malodor, normalization of hair texture, and improvement in blood smear and routine hematological findings. Based on clinical findings, laboratory results, and therapeutic response, the patient was diagnosed with emaciation accompanied by Malasseziosis and Ehrlichiosis and showed a favorable response to treatment, resulting in significant clinical improvement and stable condition after 28 days of monitoring. Dog owners are advised to ensure adequate nutrition, proper kennel sanitation, and environmental hygiene to prevent disease recurrence.